Staff’s and Managers’ Conceptions of Participation for Adults with Profound Intellectual Disabilities or Profound Intellectual and Multiple Disabilities - Lena Talman; Jenny Wilder; Jonas Stier; Christine Gustafsson (Scandinavian Journal of Disability Research, 2019)
One goal of disability policies in Sweden and other countries is to ensure that people with disabilities are afforded an equal level of daily life participation as other citizens. However, few studies have examined this in adults with profound intellectual disabilities (PID) or profound intellectual and multiple disabilities (PIMD). This study used a phenomenographic approach to interview managers and staff at a social care organisation in a medium-sized Swedish municipality. It aimed to elucidate and describe conceptions of participation to highlight conceptual variations. Divergent conceptualisations were found, reflecting a lack of organisational consensus about the meaning of participation. Trying to fulfil policy goals of daily life participation for adults with PID or PIMD without a common understanding of the meaning of participation is difficult, so people at all levels of an organisation need to have a shared understanding and definition of it.